2009
DOI: 10.1038/ajg.2009.28
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of the Bedside Index for Severity in Acute Pancreatitis Score in Assessing Mortality and Intermediate Markers of Severity in Acute Pancreatitis

Abstract: The BISAP score represents a simple way to identify patients at risk of increased mortality and the development of intermediate markers of severity within 24 h of presentation. This risk stratification capability can be utilized to improve clinical care and facilitate enrollment in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
165
2
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(190 citation statements)
references
References 23 publications
14
165
2
9
Order By: Relevance
“…Th e Markers of Severity in Acute Pancreatitis (MOSAP) cohort was developed at BWH, in Boston, MA ( 14,24 ). AP patients directly admitted or transferred to BWH from 2005 through 2009 were prospectively recruited.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…Th e Markers of Severity in Acute Pancreatitis (MOSAP) cohort was developed at BWH, in Boston, MA ( 14,24 ). AP patients directly admitted or transferred to BWH from 2005 through 2009 were prospectively recruited.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…Regarding severe AP, the Atlanta classification establishes the Ranson 8 or APACHE II 9 criteria for characterization of severity. These methods, however, have limitations reported by other studies [10][11][12][13][14][15] . In 2008, the review of the Atlanta classifivcation 16 defined the severity of acute pancreatitis, at least in the first week, is based on clinical components and suggested that the persistence of a systemic inflammatory response syndrome and / or organ failure should be considered.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 55%
“…We observed seven patients with organ failure among the dead in a week of hospitalization. However, despite its use established in the Atlanta classification 4 , it is a method that requires 48 hours to complete the evaluation, hampering the analysis within the first 24 hours, which is important in view of the prevention of possible adverse events [10][11][12] .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The Ranson and modified Glasgow score contain data not routinely collected at the time of hospitalization. 1,2 Both require 48h to complete, missing a potentially valuable early therapeutic window. [1][2][3] The APACHE II was originally developed as an intensive care instrument and requires the collection of a large number of parameters, some of which may not be relevant to prognosis in acute pancreatitis.…”
mentioning
confidence: 99%
“…1,2 Both require 48h to complete, missing a potentially valuable early therapeutic window. [1][2][3] The APACHE II was originally developed as an intensive care instrument and requires the collection of a large number of parameters, some of which may not be relevant to prognosis in acute pancreatitis. 4,5 There is a need for a simple and clinically oriented severity scoring system that can predict severity of acute pancreatitis within 24h of presentation.…”
mentioning
confidence: 99%